Real-time measurement of PMA-induced cellular alterations by microelectrode array-based impedance spectroscopy. (October 2006) - Rothermel, Andrée; Nieber, Matthias; Müller, Jana; Wolf, Peter; Schmidt, Maik; Robitzki, Andrea A.
For a feasible and cost-effective impedance measurement of cellular alterations in real-time, we combined commercially available microelectrode arrays (MEAs), consisting of 60 micro-electrodes, with a conventional impedance analyzer. For proof of principle, a breast carcinoma cell line (MCF-7) was cultured on MEAs, and cellular alterations were measured by impedance spectroscopy at a frequency ranging from 10 Hz to 1 MHz. Cells were stimulated with phorbol 12-myristate 13-acetate (PMA) at different concentrations to activate protein kinase C (PKC)-mediated extra- and intracellular changes. By addition of 0.03 µM PMA, an increase of the relative impedance (Zrel ) was observed after 10 min with a maximum at 1 kHz. Moreover, a gradual elevation of the impedance was measured 60 min after stimulation with PMA. If 0.3 µM PMA was applied, the maximal amplitude of the relative impedance after 60 min shifted from 1 kHz (0.03 µM PMA) to 150 Hz. Subsequently, the impedance was further increased up to 90 min after PMA application, after which the impedance reduced after 240 min. Since we could use MEAs for at least 10 times without affecting the sensitivity, our study revealed that commercially available MEAs comprising nanocolumnar titanium nitrite electrodes are suitable microstructures for a highly reproducible and cost-effective multisite measurement of intracellular processes by impedance spectroscopy.